The Use of Contextual Teaching Learning (CTL) With Inquiry Techniques Can Increase Students’ Motivation in Learning Aqidah Morals - HASNIDAR (International Journal of Management and Education in Human Development, 2023)
This study aims: to find out whether the CONTEXTUAL TEACHING LEARNING (CTL) approach is used. Using the INQUIRY technique in learning Aqidah Moral in Class IX at MTs Negeri 2 Kendari Can it Increase Student Learning Motivation? This research is in the form of Classroom Action Research (CAR). Data Collection Method Through Observation Method. Text measurement Learning outcomes. This method is used to obtain data about student test results. The condition of the teacher, the state of the students, the curriculum, and so on. The test is a technique or method used in carrying out the measurement accuracy, in which there are various questions, questions or a series of tasks that must be done or answered by students to measure behavioural aspects. Learners. The test was carried out in class IX at MTs Negeri 2 Kendari. In this study, researchers became key instruments, where researchers became data collectors in classroom action research. Researchers Also Become Planners and Executors of Classroom Actions Who Will Be Involved Directly with Students in The Research Process. Other supporting instruments that can be used are observation sheets, student activities during learning and student motivation questionnaires in learning Aqidah Moral. The Contextual Teaching Learning Approach with Inquiry techniques in learning Aqidah Moral is one of the approaches and learning techniques that can be implemented to increase student motivation in learning Aqidah Moral Students will respect and participate more in Aqidah Moral learning if students are more motivated and appreciate the knowledge, they get from the learning process.